Prediksi Performa Siswa Dengan Metode SAW (Simple Additive Weighting) - Harco Leslie Hendric Spits Warnars; Arif Fahrudin (Sekolah Tinggi Teknik - PLN, 2020)
In the world of student education is an important component where the role of students is as someone who is psychologically ready to receive lessons or other input from the school, but each student has different performance and development, therefore it is important to do monitoring so that student performance will always be monitored by the school In addition, in the process of valuing education for students also needs to be done by giving an appreciation in the form of giving gifts or just giving words and motivation so that students are able to perform better in learning and participating in other activities at school, in terms of selecting students with good performance or those who have a very declining development using the school method not only assess students by one criterion but with several criteria in order to produce a decision that can be accepted by many people. Performance Students must also be monitored by the school or the related rights.